NEW MODERN INFORMATION TECHNOLOGY IS A FACTOR IN RAISING AWARENESS, TALENT AND MORALE OF YOUNG PEOPLE - Aripova Zulfiyaxon Salijanovna (Western European Studies, 2024)
The article will show that the improvement of learning technologies depends on the proper use of modern information and communication networks in their place in the educational process.
Keywords: Information Communication; Information Technology; informatization